High-Risk Human Papillomavirus Oncogenic E6/E7 mRNAs Splicing Regulation - Zheng, Yunji; Li, Xue; Jiao, Yisheng; Wu, Chengjun (Frontiers in Cellular and Infection Microbiology, 2022)
High-risk human papillomavirus infection may develop into a persistent infection that is highly related to the progression of various cancers, including cervical cancer and head and neck squamous cell carcinomas. The most common high-risk subtypes are HPV16 and HPV18. The oncogenic viral proteins expressed by high-risk HPVs E6/E7 are tightly involved in cell proliferation, differentiation, and cancerous transformation since E6/E7 mRNAs are derived from the same pre-mRNA. Hence, the alternative splicing in the E6/E7-coding region affects the balance of the E6/E7 expression level. Interrupting the balance of E6 and E7 levels results in cell apoptosis. Therefore, it is crucial to understand the regulation of E6/E7 splice site selection and the interaction of splicing enhancers and silencers with cellular splicing factors. In this review, we concluded the relationship of different E6/E7 transcripts with cancer progression, the known splicing sites, and the identified cis-regulatory elements within high-risk HPV E6/E7-coding region. Finally, we also reviewed the role of various splicing factors in the regulation of high-risk HPV oncogenic E6/E7 mRNA splicing.